Analisis Meredam Angka Kemiskinan Melalui Pendekatan Ekonomi Hijau di Desa Pahlawan Kecamatan Tanjung Tiram Kabupaten Batu Bara - Annisa Ilmi Faried (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
Pahlawan village continues to experience an increase in population each year which results in the village experiencing changes that are influenced by the sustainability of development in environmental aspects. This research is a continuation of my research entitled Analysis of the Impact of Environmental Pollution on Socio-Economic Factors in Coastal Areas. What needs to be done now is to bring together the economy and the environment by realizing the progress of the renewable economic growth that comes from nature without damaging it, meaning that environmental sustainability will guarantee the sustainability of development for generations to come. The variables that researchers use are Green Economy with education variables (X1), fishermen access (X2), health (X3), environmental management (X4), income (X5) and reducing poverty (Y). The study said education, health, income had a significant effect on the green economy. For variable fishermen access and environmental management does not significantly influence poverty reduction. While on the variables of education, health, environmental management, income simultaneously affects poverty reduction.